Recent advances in polyendocrine metabolic ovarian syndrome, formerly polycystic ovary syndrome, with emphasis on endocrine and metabolic dysfunction and cardiovascular risk - Maria Forslund; Johanna Melin; Anju E. Joham; Terhi T. Piltonen; D. Aled Rees; Helena J. Teede (Journal of Internal Medicine, 2026)
Abstract Polyendocrine metabolic ovarian syndrome (PMOS), previously known as polycystic ovary syndrome, affects 10%–13% of women of reproductive age and remains underdiagnosed despite its substantial health burden. The introduction of the new PMOS nomenclature in 2026 reflects a fundamental shift in understanding the condition as a lifelong endocrine and metabolic disorder with prominent reproductive, psychological, dermatological, and cardiometabolic consequences. Once considered primarily a reproductive disorder, PMOS is now recognized as a multisystem condition. Insulin resistance and compensatory hyperinsulinemia are central pathophysiological mechanisms linking endocrine and metabolic features to reproductive dysfunction. In PMOS, insulin resistance affects 75% of lean and 95% of overweight women. Here we focus on the metabolic features. Recent advances in epidemiology include the first systematic review and meta‐analysis examining regional variations in PMOS prevalence. In parallel, contemporary population‐based studies of unselected women have confirmed that increased risks of metabolic complications observed in selected clinical cohorts also apply at the population level and have demonstrated increased risk of major adverse cardiovascular events (MACE). These studies report an almost 3‐fold increased risk of Type 2 diabetes (OR 2.9) and MACE (HR 1.2–2.5), with cardiovascular risk diverging from approximately 35 years of age. In this review, we summarize recent advances in epidemiology, pathophysiology, metabolic dysfunction, and cardiovascular risk of PMOS, together with their implications for diagnosis and clinical management. Recognizing PMOS as an early‐life marker of cardiometabolic disease highlights opportunities for earlier diagnosis, prevention, and individualized risk stratification, supporting integrated, patient‐centered care across the life course.